Optimizing Shariah Governance Practices In Ar-rahnu Cooperatives; Insight Into Structure, Guideline Adherence, And Challenges. - Nor Fadilah Bahari; Zurina Shafii; Mustafa Mohd Hanefah (KTO Karatay University, 2024)
Non-Indexed Publication